Towards the Growth of SiGeC Epitaxial Layers for the Application in Si Solar Cells. (December 2015) - Wilhelm, Martin; Beck, Felix; Wellmann, Peter J.
Abstract: For the improvement of today's well established silicon solar cells a further significant increase in light conversion efficiency needs the consideration of multi junction aspects. In this context 3C-SiC with a bandgap of 2.3 eV has already been discussed in the past. However, an ideal bandgap match within a silicon tandem cell (Eg(Si) = 1.1 eV) requires a lower bandgap of 1.8 eV which may be reached by the incorporation of Ge in the 3C-SiC lattice. In this work we report on the growth of Si-Ge-C hetero-epitaxial layers on silicon in a MOCVD reactor. A major obstacle in realizing a high Ge-content in the cubic 3C-SiC lattice is the strong trend towards segregation and phase separation in the ternary system. In terms of the atomic diameter, Ge should be more likely to substitute Si in the SiC lattice. However, concerning the excess energy the bond between Ge and C is not supposed to be stable. We will present several growth runs at different precursor flow-rates and different temperatures in the range of 1090 °C - 1330 °C and discuss the appearance of a SiGe phase. In order to detect the different bonds in the layers, especially Ge-C bonds, the samples were investigated by means of Raman-spectroscopy and x-ray diffraction. The Ge concentration was investigated by EDX measurements. No proof for the formation of Ge-C was found so far.